PENGARUH PENGALAMAN AUDITOR, INDEPENDENSI DAN KOMPETENSI TERHADAP KUALITAS AUDIT DENGAN ETIKA AUDITOR SEBAGAI VARIABEL MODERASI - Irawan, Bambang; Pratama, Diandra Ayu; Hayati, Fitria; Damayanti, Griselda; Muhsin, Muhsin (Jurusan Akuntansi, Fakultas Ekonomi dan Bisnis, Universitas Tanjungpura, 2023)
This research aims to examine and analyze the effect of auditor experience, independence, and competence on auditor quality in FEB UNTAN students who take Auditing 2 courses and examine and analyze the ability of auditor ethics to moderate the relationship between auditor experience, independence, and competence.The population used in this study means FEB UNTAN students who take the Auditing 2 course using a purposive sampling method. The number of samples is 60 students. The sample in this study was determined using a survey method, namely by distributing questionnaires personally to the respondents. The method of analysis of this research uses the Structural Equation Modeling (SEM) data analysis technique using the WarpPLS version 8.0 application.The results obtained from this research indicate that auditor experience has a positive effect on audit quality. Independence has no effect on audit quality. And competence has a positive effect on audit quality. For auditor ethics, it cannot moderate the impact of audit experience, independence, and competence on FEB UNTAN students taking Auditing 2 courses.